Clemente de Jesús Munguía Núñez (Mexico, 1810–68) - Adame, Jorge (My University, 2021)
This chapter offers a synthetic exposition of the main features of the life and work of Clemente de Jesús Munguía, known mainly for his tenacious work defending the rights of the Catholic Church against the secular liberal state, and for his writings of philosophy and theology. The biography is divided into three stages. The first (1810–40) corresponds to his childhood and youth and concludes with his graduation as a lawyer and his early professional practice in Morelia and Mexico City. The second (1841–51) begins with his ordination as a priest and continues with his work as rector at the Seminary of Morelia, where he profoundly reformed the curriculum and wrote his most important books on theology and moral philosophy. The third stage (1852–68) begins with his ordination as Bishop of Morelia, which generated political controversy over the oath that the government required for him to be ordained; this stage continues with his constant defense of the rights of the Church against the excessive pretensions of liberal governments and the government of Emperor Maximilian, and it concludes with his exile and death in Rome. ©2021 Routledge.
Clemente de Jesús Munguía Núñez (México, 1810-1868)
Clemente de Jesus Munguia Nunez (Mexico, 1810-1868)
Keywords: Church and state -- Latin America; Ecclesiastical law -- Latin America; Religion and law -- Latin America